2020
DOI: 10.14336/ad.2019.0718
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Nurr1 as a Mediator and Therapeutic Target in Alzheimer’s Disease-related Pathogenesis

Abstract: Several studies have revealed that the transcription factor nuclear receptor related 1 (Nurr1) plays several roles not only in the regulation of gene expression related to dopamine synthesis, but also in alternative splicing, and miRNA targeting. Moreover, it regulates cognitive functions and protects against inflammationinduced neuronal death. In particular, the role of Nurr1 in the pathogenesis of Parkinson's disease (PD) has been well investigated; for example, it has been shown that it restores behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 248 publications
(357 reference statements)
0
46
0
Order By: Relevance
“…The importance of Nurr1 in PD pathology is well established [19], and reduced Nurr1 levels have been reported in AD animal models and the brains of patients with AD [112,113]. Therefore, Nurr1 has been suggested as a valid biomarker for neurodegenerative diseases and a therapeutic target [18,23]. In our studies, we reported that the pharmacological stimulation of Nurr1 could improve or restore cognitive function through adult hippocampal neurogenesis [23,38].…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The importance of Nurr1 in PD pathology is well established [19], and reduced Nurr1 levels have been reported in AD animal models and the brains of patients with AD [112,113]. Therefore, Nurr1 has been suggested as a valid biomarker for neurodegenerative diseases and a therapeutic target [18,23]. In our studies, we reported that the pharmacological stimulation of Nurr1 could improve or restore cognitive function through adult hippocampal neurogenesis [23,38].…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, Nurr1 has been suggested as a valid biomarker for neurodegenerative diseases and a therapeutic target [18,23]. In our studies, we reported that the pharmacological stimulation of Nurr1 could improve or restore cognitive function through adult hippocampal neurogenesis [23,38]. In this study, a new mechanism underlying Nurr1-mediated adult neurogenesis, i.e., through the regulation of cell cycle-related molecules, is suggested.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Nr4a2 is a nuclear receptor, also known as Nurr1, essential for the development and specification of midbrain dopamine neurons and regulated by α-syn (Decressac et al 2012). Nr4a2 expression is found to be directly induced by various stimuli such as inflammatory signals and cytokines, and although its up-regulation is often associated with protective effects, it is also an indicator of a neuroinflammatory response (Jeon et al 2020). Overall, these data suggest that CK2α’ could be modulating synaptic activity and neuroinflammation by controlling the activity of α-syn and their corresponding targets.…”
Section: Resultsmentioning
confidence: 99%